2004
DOI: 10.1002/polb.20050
|View full text |Cite
|
Sign up to set email alerts
|

Fracture morphology and mechanical properties of ethylene/vinyl acetate rubber vulcanizates reinforced by in situ prepared sodium methacrylate

Abstract: Ethylene/vinyl acetate rubber (EVM) was reinforced by sodium methacrylate (NaMAA) that was in situ prepared through the neutralization of sodium hydroxide and methacrylic acid in EVM during mixing. The mechanical properties of EVM vulcanizates with different NaMAA loadings and at different crosslink densities were studied and compared with those of high abrasion furnace carbon black (HAF) filled EVM vulcanizates. The fracture surfaces of gum and filled EVM vulcanizates were observed with scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Thus, not only conventional covalent crosslinks but also ionic crosslinks which exhibit special crosslinking structure and morphology coexist in the metal salts of unsaturated carboxylic acids‐reinforced rubbers [10]. Although the nano‐particles have been observed under transmission electron microscopy (TEM) [5, 6, 14], and many microstructure models [15] have been proposed, some aspects still need to be studied to improve the recognition of the essential microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, not only conventional covalent crosslinks but also ionic crosslinks which exhibit special crosslinking structure and morphology coexist in the metal salts of unsaturated carboxylic acids‐reinforced rubbers [10]. Although the nano‐particles have been observed under transmission electron microscopy (TEM) [5, 6, 14], and many microstructure models [15] have been proposed, some aspects still need to be studied to improve the recognition of the essential microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the observed nonlinear behavior of the samples cured for 1 min supports the polymerization of MDMA, which provide the ionic crosslinks. This also have mentioned in the introduction 5–9. For large strain (λ −1 is 0.4–0.2), increasing of σ/2(λ − 1/λ 2 ) is due to that the end‐to‐end distance of the chains tends to its inextensible limit due to the crosslinked network.…”
Section: Resultsmentioning
confidence: 75%
“…As a new type of reinforcing agent for rubbers, and with homopolymerization and graft‐polymerization taking place in the rubber matrix, metal salts of unsaturated carboxylic acids can be polymerized to form nanodispersion phases acting as nanoparticles and to graft onto rubber chains to enhance the crosslinked network during peroxide curing. The ionic crosslinks are formed by metal salts graft‐polymerized onto the rubber chains, whereas the poly‐(metal salt) chains separate from the rubber matrix and aggregate into nano‐scaled fine particles, forming salt crosslinks 5–9. As a result, rubbers with metal salts of unsaturated carboxylic acids contain not only conventional covalent crosslinks but also ionic crosslinks and exhibit special crosslink structure and morphology 5–9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Little study has focused on MHs treated with unsaturated carboxylic acid, such as methacrylic acid (MAA). On the other hand, the reinforcement of rubbers by the addition or in situ preparation of metallic methacrylates, such as magnesium methacrylates (MDMAs), [14][15][16] sodium methacrylates, 17,18 or zinc methacrylates, 19,20 has attracted the extensive attention of researchers. Yin et al 21 reported that a small amount of MAA obviously enhanced the mechanical properties of peroxidecured styrene-butadiene rubber vulcanizates filled with aluminum hydroxide; this indicated that MAA could also be used as an effective coupling agent.…”
Section: Introductionmentioning
confidence: 99%